1999
DOI: 10.1007/s004030050389
|View full text |Cite
|
Sign up to set email alerts
|

Cultured fibroblasts from chronic diabetic wounds on the lower extremity (non-insulin-dependent diabetes mellitus) show disturbed proliferation

Abstract: Patients with diabetes mellitus experience impaired wound healing often resulting in chronic foot ulcers. Hospital discharge data indicate that 6-20% of all diabetic individuals hospitalized (mostly with type 2 diabetes) have a lower extremity ulcer. Maintaining glucose levels at acceptable levels (below 10 mmol/l) is considered to be an important part of the clinical treatment, but the exact mechanism by which diabetes delays wound repair is not yet known. We studied this phenomenon by determining the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
145
0
14

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(169 citation statements)
references
References 22 publications
10
145
0
14
Order By: Relevance
“…Evidence from studies of fibroblasts from diabetic ulcers have shown similar abnormalities (Loots et al, 1999;Loot et al, 2002). The microenvironment of the wound is likely to be another important determinant of cellular selection and phenotypic expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from studies of fibroblasts from diabetic ulcers have shown similar abnormalities (Loots et al, 1999;Loot et al, 2002). The microenvironment of the wound is likely to be another important determinant of cellular selection and phenotypic expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence in support of this hypothesis, much of it developed in the context of diabetic and venous ulcers. Fibroblasts cultured from diabetic ulcers show decreased mitogenic potential and differential responses to certain cytokines, either along or in combination (Loots et al, 1999;Loot et al, 2002). It has been shown that dermal fibroblasts cultured from venous ulcers are senescent (Stanley and Osler, 2001), show decreased proliferative potential (Stanley et al, 1997), and are unresponsive to stimulation by such critical growth factors as transforming growth factor-b1 (TGF-b1) (Hasan et al, 1997) and platelet-derived growth factor BB (PDGF-BB) (Agren et al, 1999).…”
mentioning
confidence: 99%
“…132 A consistent finding in pressure ulcers, the diabetic foot and venous stasis ulcers is an accumulation of senescent fibroblasts. [133][134][135] These fibroblasts demonstrate decreased proliferative rates and a dysfunctional chemokine secretory profile involving excess CCL2 release and reduced CXCL8 production compared with wounds healing normally. 136,137 Furthermore, high levels of functional CCL2, CCL5, CCL18, CCL20, CCL27, CXCL1, and CXCL12 have been reported in chronic wound debridement tissue.…”
Section: 117mentioning
confidence: 99%
“…Dermal fibroblast proliferation is a major feature of cutaneous wound healing (Martin, 1997), which is altered in several pathologies such as keloids (Calderon et al, 1996) and chronic wounds, which can evoluate toward cutaneous carcinoma (Loots et al, 1999;Chraibi et al, 2004). To date the mechanisms underlying cell proliferation in the cutaneous wound healing context remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%